2012
DOI: 10.1007/s11908-012-0238-8
|View full text |Cite
|
Sign up to set email alerts
|

Dacryocystitis: Systematic Approach to Diagnosis and Therapy

Abstract: The objective of this paper is to review the main findings of the largest studies on the etiopathogenesis and microbiology of the development of dacryocystitis and to formulate clinical and surgical guidelines based on said studies and on our experience at Cruces Hospital, the Basque Country, Spain. The most common sign of this entity is the distal nasolacrimal duct obstruction, and this should be treated to prevent clinical relapse. The time when surgery should be indicated mainly depends on the clinical sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 41 publications
0
37
0
2
Order By: Relevance
“…The same authors (18) demonstrated a statistically significant similarity between isolates from lacrimal and nasal/conjunctival samples and stated that the commensal flora of the nose and conjunctiva may have a direct role in the pathogenesis of chronic dacryocystitis. They obtained culture specimens directly from the lacrimal sac under an operating microscope and emphasized the reduced contamination during sample collection associated with this technique compared to the other methods of collection, such as applying pressure over the lacrimal sac or waiting for purulent material to exit the lacrimal sac via reflux (9) . The microorganism growth rates from lacrimal sac samples, involved and contralateral side conjunctival and nasal samples obtained preoperatively, and involved conjunctival samples obtained at first and second postoperative week were 56.7%, 40%, 23.3%, 98.9%, 97.8%, 12.2%, and 5.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors (18) demonstrated a statistically significant similarity between isolates from lacrimal and nasal/conjunctival samples and stated that the commensal flora of the nose and conjunctiva may have a direct role in the pathogenesis of chronic dacryocystitis. They obtained culture specimens directly from the lacrimal sac under an operating microscope and emphasized the reduced contamination during sample collection associated with this technique compared to the other methods of collection, such as applying pressure over the lacrimal sac or waiting for purulent material to exit the lacrimal sac via reflux (9) . The microorganism growth rates from lacrimal sac samples, involved and contralateral side conjunctival and nasal samples obtained preoperatively, and involved conjunctival samples obtained at first and second postoperative week were 56.7%, 40%, 23.3%, 98.9%, 97.8%, 12.2%, and 5.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A unique combination of stasis and moisture in NLDO may create an optimal environment for the growth of lacrimal sac flora. Numerous bacterial species have been implicated in chronic dacryocystitis (9) . Furthermore, the types of isolated pathogens may change over time (10,11) .…”
Section: Introductionmentioning
confidence: 99%
“…9 Treatment of both preseptal and orbital cellulitis should begin with amoxicillin/clavulanate 875 mg orally, 2 times daily for 10 days, but if that is not available, then oral fluoroquinolones (such as moxifloxacin) may be substituted. 12 If the practitioner is certain that an infection is isolated to the preseptal space, evacuation can be nonemergent. However, if there is any question that the infection may involve the orbit, or a presumed preseptal cellulitis is not responding to antibiotic treatment, evacuation should be emergent.…”
Section: Periocular Inflammationmentioning
confidence: 99%
“…Several bacteria have been implicated as causative agents of chronic dacryocystitis. (1) Due to inadvertent use of antibiotics and microbiological resistance, there is a change in the spectrum of agents responsible for chronic dacryocystitis. (2) Knowledge of the microbial organisms and bacteria responsible for chronic dacryocystitis in a particular geographical area is essential in choosing appropriate antibiotics.…”
Section: Introductionmentioning
confidence: 99%